Experimental investigation on mass flow rate measurements and feeding characteristics of powder at high pressure. (5th June 2016) - Sun, Haijun; Hu, Chunbo; Zhang, Tian; Deng, Zhe
Highlights: IMM can be used to measure mass flow rate of powder fuel in firing condition. Two ways can be used to adjust powder mass flow rate in powder motor. Pipe cross sectional area affects more than pressure when adjusting thrust. Differences between experimental and equilibrium gas–solid flow theoretical results. Abstract: The powder fuel feeding system is the key component of powder engine with multiple ignition capability and thrust modulation function. In cold state, the experiments of powder fuel mass flow rate measurement and powder feeding characteristics at high pressure were carried out. By comparing two measuring methods, the veracity of indirect measuring method was verified, which shows that can be applied to flow rate monitoring in the process of engine ignition. Otherwise, there are two main approaches to adjust powder mass flow: changing initial fluidized pressure or changing the cross sectional area of pipe. The powder mass flow rate is linear with these variable parameters. The experimental results were also compared with theoretical values calculated by gas–solid choking theory, which turns out that the theoretical values are higher than experimental results. It shows the gas solid choking theory needs to be corrected based on nonequilibrium gas–solid flow model.